Cardiotoxicity of anti-cancer drugs: cellular mechanisms and clinical implications - Kwok, Cecilia; Nolan, Mark (Frontiers in Cardiovascular Medicine, 2023)
Cardio-oncology is an emerging field that seeks to enhance quality of life and longevity of cancer survivors. It is pertinent for clinicians to understand the cellular mechanisms of prescribed therapies, as this contributes to robust understanding of complex treatments and off-target effects, improved communication with patients, and guides long term care with the goal to minimise or prevent cardiovascular complications. Our aim is to review the cellular mechanisms of cardiotoxicity involved in commonly used anti-cancer treatments and identify gaps in literature and strategies to mitigate cardiotoxicity effects and guide future research endeavours.